3D-printed cellular tips for tuning fork atomic force microscopy in shear mode - Liangdong Sun (Nature Portfolio, 2020)
The authors investigate 3D-printed tips, based on controlled microstructural architectured materials, as probes for shear-mode atomic force microscopy. They demonstrate that the tailored stiffness and energy-absorbing behaviour of the material are beneficial for improving image quality.